Characterization Investigations Of A Mechanically Alloyed And Sintered Al-2 Wt%Cu Alloy Reinforced With Wc Particles - Evirgen, Alper; Ovecoglu, M. Luetfi (Aperta, 2010)
Elemental powders of Al, Cu and WC were mechanically alloyed in a high energy mill for milling durations of 1 h, 2 h, 3 h and 5 h to constitute the Al-2Cu-7WC (wt%) composition. The microstructural characterizations of powders were performed with SEM and XRD analyses and additionally microhardness tests were applied for mechanical characterization. DSC and post-XRD tests were carried out to study the phase transformations in powder form. The MA'd powder pellets were sintered under inert Ar atmosphere at 650 degrees C for 4 h. XRD, SEM, and EDS investigations and microhardness measurements were conducted for the microstructural and mechanical characterization of sintered samples. DSC and XRD examinations of powders MA'd for 5 h showed that decomposition of WC after 450 degrees C led to the formation of Al12W intermetallic which provided high strength composites. The XRD and SEM investigations revealed the presence of Al12W phase in all sintered samples. Microhardness of sintered samples increased with the increase of MA duration. A maximum Vickers hardness of 201 HV and a maximum sinter density of 93.3% have been observed for the sample MA'd for 5 h. (C) 2010 Elsevier B.V. All rights reserved.